شوێنى ئایین و مەزهەب لە دابەشکارییەکانى (سایکس بیکۆ) دا چارەنوسى دابەشکردنى کوردستان بە نموونە - فه‌تاح, ماجید خه‌لیل (Sulaimani Journal for Humanities, 2018)
Research abstract The role of doctrine and religion in Subdivisions Sykes-Picot The fate of Kurdistan as a case of study the role and impacts of Mysticism and religious doctrines and religious minorities in territories of ottoman empire and Iranian became suitable situation in order to western countries start to intervention of interior affairs in to both of countries. Also religious and doctrines of different nations have significant role on many of mystery and political agreements during the First World War. Kurdish nation have many different religious doctrines. That is why; religious doctrines have great impact on the fate of Kurdistan and Kurdish people Subdivisions. Western countries have exact focus on Kurdish religious and doctrines uprisings. Western countries especially Britain used the religions and doctrines of Kurdistan for sake of their interests. They treated with Kurdish emotion like Iranian and Ottoman Empire. This research is divided in to three parts. The first is dedicated to the role of religion and doctrines in Subdivisions Sykes-Picot. Second part is about the situation of Kurdish nation and the role of Kurdish doctrines during the First World War. Third part is dedicated to the role of Kurdish religion and doctrine in Subdivisions Sykes-Picot.